Hungary Skilling Up the Next Generation : An Analysis of Hungary’s Performance in the Program for International Student Assessment - World Bank Group (World Bank, Washington, DC, 2015)
Facing the prospects of rapid aging and demographic decline over the coming decades, Hungary needs a highly skilled workforce to help generate the productivity growth that it needs to continue fueling a convergence of its living standards with those of its West European neighbors. Skilling up Hungary’s workforce should start by equipping youth with the right cognitive and social-emotional foundation skills. International research has identified three dimensions of skills that matter for good employment outcomes and economic growth: cognitive skills, such as literacy, numeracy, creative and critical thinking, and problem-solving; social-emotional skills and behavioral traits, such as conscientiousness, grit, and openness to experience; and job- or occupation-specific technical skills, such as the ability to work as an engineer. Hungary can do significantly better in preparing its next generation with the right cognitive foundation skills. This report focuses on cognitive skills and examines results for Hungary from the program for international student assessment (PISA), which assesses the mathematics, reading, and science competencies of 15-year-olds. This report lays out a policy agenda consisting of two parallel elements: first, improving socioeconomic conditions for children and youth in general and in school through policies targeted to the poor and disadvantaged such as welfare and employment policies for parents and education support for children. Second, promoting equity and reducing socioeconomic segregation in basic education through inclusive education policies.